2008
DOI: 10.1530/rep-07-0573
|View full text |Cite
|
Sign up to set email alerts
|

The tonicity of murine epididymal spermatozoa and their permeability towards common cryoprotectants and epididymal osmolytes

Abstract: The permeability of murine cauda epididymidal spermatozoa was determined from the swelling caused by penetrating agents at isotonicity, which lies between 422 and 530 mmol/kg. Spermatozoa were permeable to a range of solutes with size !200 Da. Relative entry rates of cryoprotective agents (CPAs) were ethylene glycolzDMSOOpropane-1,2-diolOglycerolOpropane-1,3-diol. More polar compounds including major epididymal secretions were impermeant. None of the compounds entered spermatozoa through quininesensitive chann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…However, recent studies examining the osmolality of cauda epididymal fluid found that murine spermatozoa are actually stored in a hyperosmotic milieu in cauda epididymides ranging from 375 to 500 mmol/kg (Yeung et al 1999, Cooper et al 2008. Even after ejaculation, spermatozoa are still at a slightly hyperosmotic condition in the female reproductive tract (uterine fluid is 330 mmol/kg; Yeung et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies examining the osmolality of cauda epididymal fluid found that murine spermatozoa are actually stored in a hyperosmotic milieu in cauda epididymides ranging from 375 to 500 mmol/kg (Yeung et al 1999, Cooper et al 2008. Even after ejaculation, spermatozoa are still at a slightly hyperosmotic condition in the female reproductive tract (uterine fluid is 330 mmol/kg; Yeung et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In this experimental design (termed the initial time-course protocol), spermatozoa were pre-incubated in a medium with the mean osmolality of epididymal fluid, i.e. close to isotonic conditions (Cooper et al 2008), so that osmotic challenges would be minimised during preincubation with the putative inhibitors without quinine. Thereafter, they were subjected to a physiological osmotic challenge in the drug in the absence or presence of quinine.…”
Section: Discussionmentioning
confidence: 99%
“…In the second protocol (initial time-course), the tubule contents were transferred to an albumin (4 mg/ml)-containing BWW medium with osmolality raised with NaCl to 430 mmol/kg (BWW 430 ; similar to that of epididymal fluid (Yeung et al 1999) and close to isotonic with cauda epididymidal spermatozoa (Cooper et al 2008)) for preincubation at 37 8C in the presence of water transport inhibitors but not quinine. After 10 min, the sample was transferred to BWW 330 containing 6 mg/ml PI as well as the inhibitor with or Water channels in murine spermatozoa without 800 mmol/l quinine and read immediately and continuously for 5 min in the flow cytometer.…”
Section: Animal Experimentsmentioning
confidence: 99%
“…In mice, seminal vesicle fluid is iso-osmolal with blood, 12 that is, hypotonic with respect to epididymal contents. 34 This means that cauda epididymidal spermatozoa are suddenly confronted at ejaculation with a drastic decrease in osmolality, initially in the accessory gland fluids, which expel them from the male tract, and later in the hypotonic female tract fluid. This would lead to an influx of water and cell swelling if this process were not countered by the regulatory volume decrease (RVD).…”
Section: Sperm Volume Regulation: the Fluid Environmentmentioning
confidence: 99%